(untitled) (Quinto Sol, 2014)
This article focuses on the legislative debates of the province of Buenos Aires during the period of consolidation of state institutions, with the purpose of identifying the reasons that blocked those provincial executive branch initiatives intended to limit the broad jurisdiction of the justice of the peace in criminal matters. Beyond economic and political reasons that explain the immutability of their powers, this study highlights the impact of the atmosphere of concern generated by the damaging effects of criminal policies. Because of the growth in prison population and stringency criminal law, the role of the justices of the peace would become more important as a key instance of mediation.